2017
DOI: 10.1021/acs.est.6b03294
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Brominated Compounds in Flame Retarded Plastics Containing TBBPA by Combining Isotope Pattern and Mass Defect Cluster Analysis

Abstract: The study of not only main flame retardants but also of related degradation products or impurities has gained attention in the last years and is relevant to assess the safety of our consumer products and the emission of potential contaminants into the environment. In this study, we show that plastics casings of electric/electronic devices containing TBBPA contain also a complex mixture of related brominated chemicals. These compounds were most probably coming from impurities, byproducts, or degradation product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…In recent years, the increasing number of reports of contaminants of emerging concern (CECs) presents a growing potential hazard for ecological and human health. The group of CECs includes plasticizers (phthalates, terephthalates, benzoates, sebacates, etc. ), brominated and organophosphorus flame retardants, antioxidants, UV-light stabilizers, and other chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the increasing number of reports of contaminants of emerging concern (CECs) presents a growing potential hazard for ecological and human health. The group of CECs includes plasticizers (phthalates, terephthalates, benzoates, sebacates, etc. ), brominated and organophosphorus flame retardants, antioxidants, UV-light stabilizers, and other chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that this new approach is a suitable method for the analysis and chemical fingerprint of halogenated compounds . By using nontraditional rescaling units such as −H/+Cl, CF 2 , +F/–Cl, −HBr, the plot can act help analysts to visually separate homologous (halogenated) series that are not so easily distinguishable in the original mass spectrum. …”
Section: Introductionmentioning
confidence: 99%
“…TCS has been widely used in human personal care due to its antibacterial properties, 2 and TBBPA is an important brominated flame retardant (BFR) used after the Stockholm Convention phasing out penta-and octa-BDE-based flame retardants in consumer products. 3,4 Another kind of phenolic compound is endogenous metabolites within the living body, such as hydroxyl polycyclic aromatic hydrocarbons (OH-PAHs), hydroxyl polybrominated diphenyl ethers (OH-PBDEs), and brominated phenols (BRPs). OH-PAHs and OH-PBDEs are metabolites of PAHs and PBDEs from cytochrome P450 enzyme-catalyzed hydroxylation, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Many kinds of phenols are synthetic chemicals, including triclosan (TCS) and tetrabromobisphenol A (TBBPA). TCS has been widely used in human personal care due to its antibacterial properties, and TBBPA is an important brominated flame retardant (BFR) used after the Stockholm Convention phasing out penta- and octa-BDE-based flame retardants in consumer products. , Another kind of phenolic compound is endogenous metabolites within the living body, such as hydroxyl polycyclic aromatic hydrocarbons (OH-PAHs), hydroxyl polybrominated diphenyl ethers (OH-PBDEs), and brominated phenols (BRPs). OH-PAHs and OH-PBDEs are metabolites of PAHs and PBDEs from cytochrome P450 enzyme-catalyzed hydroxylation, respectively. , BRPs were cleavage products of BFRs or OH-PBDEs through biological metabolisms. , Specifically, 2,4-dibromophenol and 2,4,6-tribromophenol are also commercial flame retardants used like TBBPA. , …”
Section: Introductionmentioning
confidence: 99%